Mission ORCA: orbit refinement for collision avoidance - Barles, Anaïs; Bilkhu, Satnam; Boulnois, Anthony; Cuesta Arija, Francisco Javier; Duarri Albacete, Guillem; Easdown, William; Estalella Silvela, Alvaro; Gallego Fernández, Ramiro; Kent, Ben; Martínez Mariscal, Javier; Martinez Mata, Alfonso; Pradeep, Shilpa; et al. (Advances in Astronautics Science and Technology, 2022)
Forecasting of collisions between resident space objects (RSOs) is becoming critical for the future exploitation of near-Earth space. A constellation of 28 spacecrafts (plus in-orbit spares) in sun synchronous orbits is proposed as a solution for improving the current space situational awareness capabilities. Each satellite uses an optical payload to track target RSOs, with the satellite's position precisely determined. Multiple pictures of the RSO are taken, and the spacecraft attitude used to calculate the target's position relative to the spacecraft. The target's orbit is then determined from the movement of the target through the field of view over time. The system outputs orbit state vectors of the tracked object, allowing precise orbit characterisation and collision forecasting to be delivered. The constellation's design allows high temporal resolution, so reliable information can be supplied to end-users. The paper shows the results of the system design of a demonstration mission meant to verify the feasibility of the concept, performed by a team of students of Cranfield University. The exercise addresses all the aspects of the preliminary design, including the definition of the mission and system requirements, the selection of the overall mission architecture, operations, and mission phases. A cap on the overall cost allows for the realisation of the platform within a university budget. The outline of the design includes not only the selection and sizing of all the subsystems and payload but also suggests a new strategy for deploying the constellation if the demonstration mission is successful. The utilisation of high TRL and COTS components, as well as mass, power, and link budgets, demonstrate the feasibility of the overall mission concept.